Investigation of university students’ critical thinking in debate: Justification for the “AREL” argumentation process - Dwiyoga Daniswara, Landry; Bambang Yudi Cahyono (Universitas Muhammadiyah Sidoarjo, 2023)
This qualitative research investigated students’ critical thinking in a debate group at a university level. It involved six students who performed a debate that used the Asian Parliamentary System. Data on students’ critical thinking were collected by using field notes and video recording. Content analysis was employed to analyze the data focusing on the use of argument traits of the AREL model. The traits consist of Assertian, Reasoning, Evidence, and Link Back (AREL). Moreover, a self-evaluation questionnaire was distributed to triangulate the students’ critical thinking levels. It was found that students’ critical thinking level was mostly below average. Four out of six students did not meet the score which is the threshold level of a high-level debater. Most of their argument traits consist of Assertion (A), Reasoning (R), and Evidence (E), leaving Link back (L) traits untouched. Interestingly, this research revealed a new finding. Many of the students used a multi-layer structure of argumentation. In practice, they occasionally used Assertions with more than one Reasoning and more than one Evidence. HIGHLIGHTS: The components of argument (argument traits) consist of Assertion, Reasoning, Evidence, and Link Back (AREL) and are used to see the argumentation process of debaters. The major argumentation process of debaters was incomplete and inconsistent since they only fulfilled Assertion, Reasoning, and Evidence (ARE). However, some might provide multi-layer argument traits as they could make more than one Reasoning and Evidence under one Assertion. The students’ or debaters’ critical thinking can be measured by the quality of their argumentation process and assessed using a questionnaire provided by Cottrell (2005).